HUBUNGAN ANTARA GAYA KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP MOTIVASI KERJA DAN KINERJA KARYAWAN (Studi Pada Karyawan PG. Djombang Baru) - Erlangga Putra Utama (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
This study aims to identify and analyze the influence of leadership style to motivation and to the influence of organizational climate to motivation of Djombang Baru Employee. In addition, to determine whether the study of some variables can affect the employee’s performance in PG. Djombang Baru. Objects are selected im this study were Djombang Baru employees. The Djombang Baru was chosen as the place to do this study because the writer is one of the Djombang Baru employee. He sees the effect of the presence of leadership style and organizational climate on how to arise motivation and employee’s performance is very important. The study was conducted over approximetly three months. The processes were introduction, finding problems, arranging proposal and composing to the thesis. This study used quantitative research approach, by formulating hypotheses then performed statistical tests to accept or reject the hypothesis. From analyzing data, testing hypothesis, and using of multiple variable analysis equipment the studies, such as validity and reliability test on each variable. The result of this study showed that the effect of each independent variable, leadership style and organizational climate to the intervening variable, motivation (Z) and employee’s performance (Y) is positive and significant. This study is consistent with research of Setiawan (2015), Nisyak (2016), and Wahyuni (2015) who states that better leadership style and organizational climat, better their motivation and performance.